A discourse analysis of media representation of women political leaders in Uganda - Kemirembe, Grace (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study is a qualitative desktop research project. The study employed a Feminist Critical Discourse Analysis to analyse and unpack the discursive ways in which female politicians are discussed and talked about in Ugandan online media. This study was a response to the realisation that online media portrayals of female politicians in Uganda remain largely unexplored. Additionally, the study discovered that the Daily Monitor and The Observer, the two newspapers that this thesis researched, often employ gender stereotypes and sexist coverage of female politicians in Uganda using personalisation, trivialisation and demonisation frames. The study illustrates that these misogynistic frames are intended to diminish women's importance in the political sphere. Moreover, women who do not conform to the gender stereotypes are portrayed as social deviants. This work concludes that one of the challenges faced by women politicians in Uganda, and in Africa as a whole, is how to exploit online media's productive capacity while, at the same time, resisting its use as an instrument that undermines them. Given the limited scope of the study using only two media organisations, future studies on media representation of female politicians could expand the range to include print and visual sources to provide generalisable results.
Keywords: Discourse analysis; Media representation; Representation (Philosophy); Women in mass media; Women politicians -- Uganda